Effects of soil insecticide treatments on northern corn rootworm, Diabrotica barberi [Coleoptera : Chrysomelidae] populations and on corn yield - Cormier, D.; Martel, P. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
A 3-yr field study was conducted to determine the effects of three soil applied insecticides on northern corn rootworm (Diabrotica barberi) populations. In each plot, an emergence cage was placed over a corn (Zea mays) plant, and adult populations were monitored weekly. Larval damage to corn roots was evaluated and corn yield was recorded at the end of the growing season. Insecticide treatments significantly reduced the number of emerging adults in the first yr, but no difference was observed in the following yr. Root strength was negatively correlated to the number of emerging adults per plant. Each yr, corn yields in treated plots did not differ significantly from yield in untreated plots, which suggests that insecticide treatments can reduce the number of emerging adults without increasing yields.